Step * 2 of Lemma flattice-order_transitivity


1. [X] Type
2. as (X X) List List
3. bs (X X) List List
4. cs (X X) List List
5. ∀b:(X X) List
     ((b ∈ bs)  ((∃x:X X. ((x ∈ b) ∧ (∃y∈b. flip-union(x) ∈ (X X)))) ∨ (∃a:(X X) List. ((a ∈ as) ∧ a ⊆ b))))
6. ∀b:(X X) List
     ((b ∈ cs)  ((∃x:X X. ((x ∈ b) ∧ (∃y∈b. flip-union(x) ∈ (X X)))) ∨ (∃a:(X X) List. ((a ∈ bs) ∧ a ⊆ b))))
7. (X X) List
8. (b ∈ cs)
9. (X X) List
10. (a ∈ bs)
11. a ⊆ b
12. X
13. (x ∈ a)
14. (∃y∈a. flip-union(x) ∈ (X X))
15. (x ∈ b)
⊢ (∃y∈b. flip-union(x) ∈ (X X))
BY
((RWO  "l_exists_iff" (-2) THENA Auto) THEN (RWO  "l_exists_iff" THENA Auto) THEN ParallelOp -2 THEN Auto) }

1
1. [X] Type
2. as (X X) List List
3. bs (X X) List List
4. cs (X X) List List
5. ∀b:(X X) List
     ((b ∈ bs)  ((∃x:X X. ((x ∈ b) ∧ (∃y∈b. flip-union(x) ∈ (X X)))) ∨ (∃a:(X X) List. ((a ∈ as) ∧ a ⊆ b))))
6. ∀b:(X X) List
     ((b ∈ cs)  ((∃x:X X. ((x ∈ b) ∧ (∃y∈b. flip-union(x) ∈ (X X)))) ∨ (∃a:(X X) List. ((a ∈ bs) ∧ a ⊆ b))))
7. (X X) List
8. (b ∈ cs)
9. (X X) List
10. (a ∈ bs)
11. a ⊆ b
12. X
13. (x ∈ a)
14. X
15. (y ∈ a)
16. flip-union(x) ∈ (X X)
17. (x ∈ b)
⊢ (y ∈ b)


Latex:


Latex:

1.  [X]  :  Type
2.  as  :  (X  +  X)  List  List
3.  bs  :  (X  +  X)  List  List
4.  cs  :  (X  +  X)  List  List
5.  \mforall{}b:(X  +  X)  List
          ((b  \mmember{}  bs)
          {}\mRightarrow{}  ((\mexists{}x:X  +  X.  ((x  \mmember{}  b)  \mwedge{}  (\mexists{}y\mmember{}b.  y  =  flip-union(x))))  \mvee{}  (\mexists{}a:(X  +  X)  List.  ((a  \mmember{}  as)  \mwedge{}  a  \msubseteq{}  b))))
6.  \mforall{}b:(X  +  X)  List
          ((b  \mmember{}  cs)
          {}\mRightarrow{}  ((\mexists{}x:X  +  X.  ((x  \mmember{}  b)  \mwedge{}  (\mexists{}y\mmember{}b.  y  =  flip-union(x))))  \mvee{}  (\mexists{}a:(X  +  X)  List.  ((a  \mmember{}  bs)  \mwedge{}  a  \msubseteq{}  b))))
7.  b  :  (X  +  X)  List
8.  (b  \mmember{}  cs)
9.  a  :  (X  +  X)  List
10.  (a  \mmember{}  bs)
11.  a  \msubseteq{}  b
12.  x  :  X  +  X
13.  (x  \mmember{}  a)
14.  (\mexists{}y\mmember{}a.  y  =  flip-union(x))
15.  (x  \mmember{}  b)
\mvdash{}  (\mexists{}y\mmember{}b.  y  =  flip-union(x))


By


Latex:
((RWO    "l\_exists\_iff"  (-2)  THENA  Auto)
  THEN  (RWO    "l\_exists\_iff"  0  THENA  Auto)
  THEN  ParallelOp  -2
  THEN  Auto)




Home Index